2014
DOI: 10.1371/journal.pone.0091559
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β Attenuates Myofibroblast Formation and Extracellular Matrix Production in Dermal and Lung Fibroblasts Exposed to Transforming Growth Factor-β1

Abstract: One of the most potent pro-fibrotic cytokines is transforming growth factor (TGFβ). TGFβ is involved in the activation of fibroblasts into myofibroblasts, resulting in the hallmark of fibrosis: the pathological accumulation of collagen. Interleukin-1β (IL1β) can influence the severity of fibrosis, however much less is known about the direct effects on fibroblasts. Using lung and dermal fibroblasts, we have investigated the effects of IL1β, TGFβ1, and IL1β in combination with TGFβ1 on myofibroblast formation, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
57
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 72 publications
14
57
0
Order By: Relevance
“…The cytokine profiles in our study are commensurate with an activation of fibrotic and inflammatory processes, which are associated with elevated levels of IL-6, IL-4, IL-1b, TNF-a, IL-10, IL-2, and INF-c (among others). 2,[26][27][28] In our study, five of the six chemokines and cytokines with the largest intergroup differences (CCL27, CCL26, CXCL6, INF-c, and CXCL11) are proinflammatory and play a major role in immunomodulation and inflammation, indicating a central role of inflammatory mechanisms in epiretinal membrane formation. Additionally, IL-10 was initially understood as a TH2 cytokine with regulatory properties in inflammatory processes, but meanwhile it was revealed that lymphocytes, macrophages, dendritic, natural killer, and mast cells also express IL-10.…”
Section: Discussionmentioning
confidence: 53%
“…The cytokine profiles in our study are commensurate with an activation of fibrotic and inflammatory processes, which are associated with elevated levels of IL-6, IL-4, IL-1b, TNF-a, IL-10, IL-2, and INF-c (among others). 2,[26][27][28] In our study, five of the six chemokines and cytokines with the largest intergroup differences (CCL27, CCL26, CXCL6, INF-c, and CXCL11) are proinflammatory and play a major role in immunomodulation and inflammation, indicating a central role of inflammatory mechanisms in epiretinal membrane formation. Additionally, IL-10 was initially understood as a TH2 cytokine with regulatory properties in inflammatory processes, but meanwhile it was revealed that lymphocytes, macrophages, dendritic, natural killer, and mast cells also express IL-10.…”
Section: Discussionmentioning
confidence: 53%
“…Myofibroblasts are responsible for the synthesis of large amounts of ECM 1, 2, 3, 4, 28. Here, we show that ACHP is able to completely abrogate the TGFβ1‐induced differentiation of both dermal and lung fibroblasts into myofibroblasts, as revealed by the inhibition of the formation of the stress fibre components αSMA and SM22α.…”
Section: Discussionmentioning
confidence: 59%
“…Regarding the performance of -1 in promoting elastin expression, con licting data regarding the inductive effects of -1 exist depending on different cell type and speci icity. ne study demonstrated the absence of an effect by -1 on elastin expression in lung ibroblasts [16,39], whereas the indings of another study were suggestive of the elastogenic effects of -1 in lung ibroblasts [40]. n the alveolar epithelial cell monolayers, -1 activated TGF-1 via RhoA v 6 integrin-dependent mechanisms [33,41].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 97%
“…The conditional expression of -1 causes severe pulmonary in lammation, alveolar hypoplasia, and progressive lung ibrosis, whereas the in vivo bloc age or depletion of -1 alleviates in lammation and ibrosis and ultimately prevents murine bronchopulmonary dysplasia [14,15]. Regarding the direct effects of -1 on the regulation of extracellular matrix (ECM) expression and composition, con licting data exist regarding the contributions of -1 to the development of myo ibroblasts, which are critical for alveolar formation [16][17][18]. Additionally, -1 induces myo ibroblast formation and elastogenesis via both an epithelial-mesenchymal transition (EMT) [19] and an endothelial-mesenchymal transition (EndoMT) [20,21].…”
mentioning
confidence: 99%